1999
DOI: 10.1097/00007890-199906270-00014
|View full text |Cite
|
Sign up to set email alerts
|

THE ALLOGENEIC RESPONSE TO CULTURED HUMAN SKIN EQUIVALENT IN THE hu-PBL-SCID MOUSE MODEL OF SKIN REJECTION1

Abstract: These results support the use of HSE and other allogeneic engineered tissues in humans provided that such tissues are limited in their antigen presenting capabilities. In addition, our findings suggest a critical function for the donor endothelial cell in rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…This model is similar to the well-characterized humanized scid mouse transplant models, which have been used to test novel immunosuppressive approaches such as CD2/LFA-3 blockade. [36][37][38] In these models human skin is engrafted on to an immunocompromised mouse and then reconstituted with allogeneic human peripheral blood mononuclear cells to induce skin allograft rejection. As murine blood vessels grow into the human skin graft and human vessels grow out of the graft, the skin acquires a dual blood supply.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This model is similar to the well-characterized humanized scid mouse transplant models, which have been used to test novel immunosuppressive approaches such as CD2/LFA-3 blockade. [36][37][38] In these models human skin is engrafted on to an immunocompromised mouse and then reconstituted with allogeneic human peripheral blood mononuclear cells to induce skin allograft rejection. As murine blood vessels grow into the human skin graft and human vessels grow out of the graft, the skin acquires a dual blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…38 Mice reconstituted with allogeneic mononuclear cells show rejection of human skin grafts that is characterized by infiltration of the skin graft with mononuclear cells and destruction of the dermo-epidermal junction (DEJ) with changes maximal at day 21 ( Figure 5c). These results are consistent with the findings of Murray et al 37 who found maximal graft infiltration and destruction between 16 and 21 days after reconstitution with allogeneic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy circumvents the need for generation of skin substitutes, which takes *3 weeks and may also eliminate the need for split-thickness autografts, thereby reducing the number of surgical operations, pain, and injury at the donor sites. Since human keratinocytes did not mount an immune response upon transplantation of skin substitutes in vivo, 50 it may be feasible to use allogeneic cells in the clinic, further reducing the time and cost of wound treatment.…”
Section: Fig 7 (Continued)mentioning
confidence: 99%
“…[74][75][76] However, these keratinocyte allografts and/or living skin equivalents will first need to be tested in vivo to determine if the MHC-deficient cells have significantly decreased immunogenicity compared with their untreated counterparts. 77 In addition to the studies described above, further manipulation of the major histocompatibility complex via the combined disruption of both class I and class II antigens could potentially permit the indefinite survival of keratinocyte allografts in patients with significant thermal injury, as class II knockout keratinocytes have been shown to be even less immunogenic than class I knockout keratinocytes, possibly as a result of the role of MHC class II antigens in the afferent arm of antigen processing, 315 in amplifying T-helper activity and ultimately in activating allospecific CTLs. 67 Indeed, this intrabody approach can be tailored to systematically evaluate different components of the antigen presentation pathways to find optimal target(s) to prevent keratinocyte allograft rejection and the rejection of other tissue engineered grafts.…”
Section: Discussionmentioning
confidence: 99%